The Role of Commissioners in Health Service Provision: Lessons Learned from Primary Care Trusts (PCTs) England - Pradhikna Yunik Nurhayati; Barbara Allen (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
It is the government’s responsibility to reach policy outcomes. Since the needs of citizen vary, the government needs to improve the way it delivers public services. Monopolistic provision of public service by government becomes inadequate to fulfill the needs of the community. One of the ways pursued by the government is working with the third sector, through procurement and commissioning. National Health Services (NHS) in the UK is one of the examples of commissioning in the healthcare service. The role of commissioning has been done by Primary Care Trusts (PCTs) from 2002 until 2014. Since commissioning became the center of public health provision, the role of commissioners has become pivotal. Using systematic review, this study aims to examine the role of commissioners in health service provision in England. It can be concluded that commissioners (PCT) play an essential role in identifying the needs of the community. This early stage of planning relied on the knowledge, skills, and capacity of commissioners. Unfortunately, not every commissioner has the capability to perform the commissioning process. Therefore, a partnership with other stakeholders is critical to overcoming the limitations of resources, including the capacity, time, and funding. The other findings suggest that national policy by the central government has contributed to the success of commissioning. Results revealed that national targets often prevented commissioners from reaching the local targets, especially when resources were insuﬃcient.